Wahibreemakhet at Saqqara: The Tomb of a Greek in Egypt - Villing, Alexandra (Zeitschrift für ägyptische Sprache und Altertumskunde, 2018)
The case of Wahibreemakhet, son of Alexikles and Zenodote, is the most prominent example for the high status that Greeks – as mercenaries or advisors – could attain in Egypt under the Saite pharaohs. The present article argues that his final resting place should be identified in a tomb at Saqqara that was probably discovered by agents of Giovanni Anastasi in the 1820s and that contained not only Wahibreemakhet’s elaborate stone sarcophagus (now in Leiden), canopic jars (in Stockholm) and shabtis (in various collections), but also a set of limestone tomb reliefs recording spells from the Book of the Dead that are today in the collection of the British Museum and that were once erroneously attributed to ‘Campbell’s tomb’ at Giza. Wahibreemakhet’s rich burial, dating to the decades around 600 BC, and his ranking title ‘Royal Sealer’ illustrate both his social status and his assimilation to Egyptian culture.